Stock-bond return correlation, bond risk premium fundamentals, and fiscal-monetary policy regime - Erica X. N. Li; Tao Zha; Ji Zhang; Hao Zhou (Federal Reserve Bank of Atlanta, 2020)
We incorporate regime switching between monetary and fiscal policies in a general equilibrium model to explain three stylized facts: (1) the positive stock-bond return correlation from 1971 to 2000 and the negative one after 2000, (2) the negative correlation between consumption and inflation from 1971 to 2000 and the positive one after 2000, and (3) the coexistence of positive bond risk premiums and the negative stock-bond return correlation. We show that two distinctive shocks-the technology and investment shocks-drive positive and negative stock-bond return correlations under two policy regimes, but positive bond risk premiums are driven by the same technology shock.
Keywords: G12; G18; E52; E62; 330; stock-bond return correlation; consumption-inflation correlation; fiscal-monetary policy regime; bond risk premium; technology shock; investment shock